Dynamic Assessments of Word Reading Skills in Diverse School-Age Children: A Meta-Analysis. - Wood, Emily; Biggs, Kereisha; Molnar, Monika (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: Dynamic assessments evaluate ability to learn and may be less biased against children who historically have underperformed on static measures that evaluate acquired knowledge. This meta-analysis examined the validity of dynamic assessments of word reading skills (phonological awareness, sound--symbol knowledge, and decoding), as measured by the strength of their correlation with performance on word reading measures. The consistency of their validity across participant reading status (typically developing vs. at risk), language status (monolingual vs. bilingual), and age group (4-5 vs. 6-7 vs. 8-9 years) was also examined to determine whether this assessment approach is an equitable means of evaluating early word reading skills. Method: Electronic databases and preprint repositories were searched to identify studies that evaluated dynamic assessments of word reading skills conducted with children between the ages of 4 and 10 years. Pearson's correlation coefficients representing the relationship between dynamic assessments and word reading measures were extracted, and an overall pooled mean effect size was calculated using a random-effects meta-analysis with robust variance estimation. Subgroup analyses for participant reading status, language status, and age group were also conducted to determine whether there were significant differences in effect sizes across groups. Results: Thirty-five studies with 192 effect sizes were identified. Overall, dynamic assessments of word reading skills demonstrated strong correlations with word reading measures (g = 0.49). Subgroup analysis by age indicated that dynamic assessments are significantly better suited to evaluate word reading in younger children (ages 4-5 and 6-7 years) than older students (ages 8-9 years; p = .0001). Validity was consistent across typically developing and at-risk participants and across bilinguals and monolinguals. There were few studies conducted with bilinguals despite dynamic assessment's purported application for this population. Conclusion: This meta-analysis provides preliminary evidence to support dynamic assessments as a valid and equitable means of evaluating word reading skills with diverse children aged 4-7 years.